The Moderating Role of Social Determinants in the Association between Malnutrition and Dental Caries Among Elementary School Children - Auliya, Suci; Djafri, Defriman; Ramadani, Mery (FKG Universitas Syiah Kuala, 2025)
Dental caries represents a significant health issue, being the most prevalent disease worldwide. Despite being easily preventable, its prevalence has not significantly decreased over the past thirty years and remains concentrated within groups of low socioeconomic status. Chronic malnutrition (stunting) in children can cause atrophy and reduced saliva secretion, which affects masticatory performance and the OHIS (Oral Hygiene Index Simplified). This study aims to determine the influence of social determinants on the correlation between stunting and dental caries in elementary school children. A cross-sectional study design was implemented, and data were analyzed using bivariate and multivariate methods. The findings of this investigation demonstrate a statistically significant association between malnutrition and dental caries (p-value = 0.010). The interaction analysis identified toothbrushing habits as a significant covariate exhibiting an interactive effect between nutritional status and the prevalence of dental caries. Following adjustment for interaction and confounding variables in the final multivariate regression model, the Prevalence Odds Ratio (POR) for nutritional status was determined to be 6.739, with a corresponding significance level of 0.007. Furthermore, the regression coefficient (B) was calculated as 1.908, indicating a positive correlation between nutritional status and the occurrence of dental caries. Based on the results of the study, it was concluded that there is a significant relationship between malnutrition and dental caries that was identified as being influenced by social determinants of toothbrushing habits.